Implementation of protected mealtimes in the subacute setting: stepped wedge cluster trial protocol. (28th February 2016) - Porter, Judi; Haines, Terry; Truby, Helen
Abstract: Aim: This protocol paper describes a study that aims to determine if protected mealtimes implementation closes the energy deficit of 1900 kJ between estimated requirements and actual energy intake of hospitalized adults in the subacute setting. Background: Protected mealtimes, a strategy developed to address the prevalence of malnourished hospitalized adults, aims to minimize unavoidable and unnecessary interruptions at mealtimes. It has been implemented widely with limited high‐quality studies as to its effect. Design: A pragmatic stepped wedge cluster trial. Primary outcomes are daily energy and protein intake. Methods: Funding was awarded in October 2014. In this study, protected mealtimes implementation will occur across each cluster (ward) chosen at random. A waiver of consent has been endorsed, enabling all patients to receive the intervention. Patients excluded from outcome evaluation will be those receiving end of life care and patients who are nil by mouth. The selection of patients for outcome evaluation will also occur randomly. Sample size, randomization, statistical analysis and contamination issues consider the reporting guidelines of the CONSORT statement: extension to cluster randomized trials. Conclusions: The methods selected will ensure that the research is of high quality with conclusions useful and relevant for translation into practice settings. The study does not aim to assess whether the intervention is sustainable beyond the study period, rather it will establish whether the removal of known barriers to intervention uptake enables high fidelity with the intervention. As a result we will have a greater understanding of the nutritional consequences of protected mealtimes in subacute care.